L'antiga universitat dominica de Tortosa (1529-1717). - QUEROL COLL, ENRIC (Scripta, 2020)
This paper explains the history of the dominican Convent-university of Tortosa. This institution, founded in 1529, was entitled to award degrees in arts and theology until the merging of all Catalan universities into the new center of Cervera, in 1717. The well-known and prestigious University of Tortosa attracted students all over the Crown of Aragon. Though the center was disallowed to confer degrees, the 1717 abolishment was not the end of the pedagogical activity, which continued until the foundation of a conciliar Seminary, in 1824.